Campuran Produk Berbasis Alami dan Perawatan Mulut Dasar untuk Pengelolaan Mukositis Mulut dan Xerostamia bagi Pasien Kanker - Prakartini, Entin; Novieastari, Enie; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe the effectiveness of oral care using mouthwash or using herbal solutions to reduce the severity, value of pain, incidence of mucositis and xerostomia and other oral symptoms such as dysphagia for cancer sufferers. This research method uses a literature review by searching articles in 6 trusted databased such as PubMed, ScienDirect, Scopus, Springer, ProQuest and EBSCHost. The results of this study showed that eleven articles out of thirteen showed the effectiveness of herbal solutiona as mouthwash in reducing mucositis and xerostomia. Two of them are the use of herbal solutions which can reduce xerostomia, bad breath and increase the rate of saliva for those undergoing hemodialysis. In conclusion, oral care interventions using mouthwash and herbal solutions as mouthwash and herbal solutions as mouthwash are effective, safe and can be used to reduce mucositis and xerostamia for cancer patients. Keywords : Mucositis, Cancer Patients, Oral Care, Xerostomia